PENGARUH STRESOR KERJA INDIVIDU TERHADAP KINERJA PEGAWAI DI DINAS PEKERJAAN UMUM KOTA PONTIANAK - Rizky Apriani E.01110010 (FISIP Universitas Tanjungpura, 2014)
This research is meant to analyze the influence of individual job stressor on the performance of employees in the Dinas Pekerjaan Umum Kota Pontianak. The problems identified in the title of this research is work overload received by each employee in Water Resources and Control in Dinas Pekerjaan Umum Kota Pontianak that can cause stress on job and degrade performance. Insufficient number of employees has also led Dinas Pekerjaan Umum Kota Pontianak delegated a lot of work to one person.The results showed that individual job stressors with employee performance has a strong relationship with the calculation of correlation of 0,671. Individual job stressors also also a negative effect on employee performance as evidenced by F test of 14,777 and 3,844 by T test with significance 5%. This means that the higher the stress experienced by employees, the lower employee performance. Simple linear regression calculation results show that the individual job stressors have a significant effect on the performance of employees in the Dinas Pekerjaan Umum Kota Pontianak especially on the Water Resources and Control at 45,1% and 54,9% determined by other factors. The writer suggestion are the employee should overcome the stress on job to all individual by positive ways like doing outbond, recreation, getting close to the mighty Lord, and other, because the good performance is supported by the controlled level of job stress. Keyword: Individual Job Stressor and Performance of Employees